Roles of bacteriophage T4 gene 5 and gene s products in cell lysis. - Kao, S H (1980)
Previous studies indicated that (i) T4 gene s product (gps) protects infected cells from superinfection lysis from without, (ii) the absence of gps in infected cells also leads to lysis from within even when T4 e lysozyme is absent, (iii) T4 gene 5 product (gp5), a polypeptide of the virion baseplate, may be responsible for inducing lysis from without, and (iv) altered gp5 of the T4 mutant 5ts1 can replace e lysozyme to cause lysis from within. Results of this study showed that (i) wild-type gp5 in infected cells lacking e lysozyme was responsible for lysis from within in the absence of gps, and (ii) gps did not protect infected cells from superinfection lysis from without by 5ts1 phage. We prpose that gps normally prevents functional expression of wild-type gp5 activity from either side of the cell wall, whereas the 5ts1 form of gp5 is insensitive to the gps barrier and induces lysis from either side of the cell wall.